Indefinite integral follows the formula: `int f(x) dx = F(x)+C`

where:

`f(x)` as the integrand function

`F(x)` as the antiderivative of `f(x) `

`C` as constant of integration.

The given integral problem: `int cot^4(theta) d theta` resembles one of the formulas from the integration table. It follows the integration formula for cotangent function as :

`int cot^n(x) dx = - (cot^((n-1))(x))/(n-1) - int cot^((n-2)) (x) dx` .

Applying the formula, we get:

`int cot^4(theta) d theta =- (cot^((4-1))(theta))/(4-1) - int cot^((4-2)) (theta) d theta`

`=- (cot^3(theta))/3 - int cot^2(theta) d theta`

To further evaluate the integral part: `int cot^2(theta) d theta` we may apply trigonometric identity: `cot^2(theta) =csc^2(theta) -1` .

`int cot^2(theta) d theta =int [csc^2(theta) -1] d theta`

Apply basic integration property:` int (u-v) dx = int (u) dx - int (v) dx.`

`int [csc^2(theta) -1] d theta =int csc^2(theta) d theta - int 1 d theta`

`= -cot(theta) - theta +C`

Note: From basic integration property: `int dx = x` then` int 1 d theta = int d theta = theta` .

From the integration table for trigonometric function, we have` int csc^2(x) dx = - cot(x)` then `int csc^2(theta) d theta=-cot(theta` ).

applying `int [cot^2(theta)] d theta=-cot(theta) - theta +C` , we get the complete indefinite integral as:

`int cot^4(theta) d theta =- (cot^3(theta))/3 - int cot^2(theta) d theta`

`=- (cot^3(theta))/3 -(-cot(theta) - theta) +C`

`=- (cot^3(theta))/3 + cot(theta) + theta +C`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.